Application of a TNF-alpha-inhibitor into the scala tympany after cochlear electrode insertion trauma in guinea pigs: Preliminary audiologic results. (November 2014) - Ihler, Friedrich; Pelz, Sabrina; Coors, Melanie; Matthias, Christoph; Canis, Martin
Abstract Objective: Cochlear implantation trauma causes both macroscopic and inflammatory trauma. The aim of the present study was to evaluate the effectiveness of the TNF-alpha inhibitor etanercept applied after cochlear implantation trauma on the preservation of acoustic hearing. Design: Guinea pigs were randomly assigned to three groups receiving cochlear implantation trauma by cochleostomy. In one group, the site was sealed by bone cement with no further treatment. A second group was additionally implanted with an osmotic minipump delivering artificial perilymph into the scala tympani for seven days. In the third group, etanercept 1 mg/ml was added to artificial perilymph. Hearing was assessed by auditory brainstem responses at 2, 4, 6, and 8 kHz prior to and after surgery and on days 3, 5, 7, 14, 28. Study sample: Fifteen healthy guinea pigs. Results: The trauma led to threshold shifts from 50.3 dB ± 16.3 dB to 68.0 dB ± 19.3 dB. Hearing thresholds were significantly lower in etanercept-treated animals compared to controls on day 28 at 8 kHz and from day 3 onwards at 4 and 2 kHz (p < 0.01; two-way RM ANOVA / Bonferroni t-test). Conclusion: The application of etanercept led to preservation of acoustic hearing after cochlear implantation trauma.